Complementary Standoff Chemical Imaging to Map and Identify Artist Materials in an Early Italian Renaissance Panel Painting1. Issue 50 (15th October 2014) - Dooley, Kathryn A.; Conover, Damon M.; Glinsman, Lisha Deming; Delaney, John K.
Abstract Two imaging modalities based on molecular and elemental spectroscopy were used to characterize a painting by Cosimo Tura. Visible‐to‐near‐infrared (400–1680 nm) reflectance imaging spectroscopy (RIS) and X‐ray fluorescence (XRF) imaging spectroscopy were employed to identify pigments and determine their spatial distribution with higher confidence than from either technique alone. For example, Mary's red robe was modeled through the distribution of an insect‐derived red lake (RIS map) and lead white (XRF lead map), rather than a layer of red lake on vermilion. The RIS image cube was also used to isolate the preparatory design by mapping the reflectance spectra associated with it. In conjunction with results from an earlier RIS study (1650–2500 nm) to map and identify the binding media, a more thorough understanding was gained of the materials and techniques used in the painting.